Socio-demographic characteristics and risk factors for HIV transmission in female bar workers in sub-Saharan Africa: a systematic literature review - Peter Dambach; Bathsheba Mahenge; Irene Mashasi; Aisa Muya; Dale A. Barnhart; Till W. Bärnighausen; Donna Spiegelman; Guy Harling (BMC, 2020)
Abstract Background Although sex workers are considered a key population in the HIV epidemic in sub-Saharan Africa (SSA), less consideration has been given to female bar workers (FBW), whose primary occupation is not sex work but who often engage in transactional sex. Understanding FBWs' risk profiles is central to designing targeted HIV prevention interventions for them. This systematic review describes the socio-demographic characteristics and risk factors for HIV transmission among FBWs in SSA. Methods We searched six databases: PubMed, Google Scholar, Web of Science, Popline, Embase and additionally the World Health Organization's WHOLIS database for grey literature between July and September 2017. Inclusion criteria were reporting (1) primary socio-demographic or behavioral data; on (2) women who sold or delivered drinks to clients; (3) in establishments serving alcohol; (4) in SSA. We excluded studies not presenting separate data on FBWs. We extracted quantitative and qualitative data from the selected studies and conducted a qualitative synthesis of findings. Results We found 4565 potentially eligible articles, including duplicates. After applying inclusion and exclusion criteria, we retained 19 articles. FBWs often migrated from rural to urban areas due to economic need or social marginalization. They began bar-based transactional sex due to low wages, peer pressure and to increase financial independence. FBWs had high HIV risk awareness but low agency to negotiate condom use, particularly with regular partners or when offered higher prices for condomless sex. FBWs were also vulnerable to violence and stigmatization. Conclusions FBWs are a vulnerable population for HIV infection. Despite social stigmatization and elevated risk of contracting STIs, bar work remains attractive because it enables unskilled women to both, make a living and maintain some independence. FBWs face HIV-related risk factors at the individual, community and societal level and may benefit from biomedical, behavioral and structural interventions.